Temperature-dependent peel performance of adhesively rebonded hybrid joints - Srinivasan, Dharun Vadugappatty (2020)
Structural bond integrity of reassembled (adhesively bonded) hybrid joints is assessed through floating roller peel tests in remanufacturing. Improper peeling, inconsistencies in the surface preparation and residual adhesive significantly affect the floating roller peel behavior of adhesively bonded and rebonded joints. In this work, the peel behavior of hybrid joints consisting of glass fiber reinforced polymer (GFRP) composite, Ti-6Al-4V adherends (with different surface preparations) and structural epoxy adhesive as a function of temperature was measured. Further, the peel performance of rebonded joints made up of thermo-mechanically debonded composites without removing the residual epoxies (R1) and reconditioned with multiple surface preparation techniques (R2) were evaluated. In this paper, the effect of residual adhesive on the peel load, failure modes as a function of temperature and flexural deformation of the Ti-6Al-4V adherend were studied. Improper surface reconditioning of debonded composites resulted in poor bond quality and peel strength as compared to the pristine joints.